A rapid 3D magnetotelluric forward approach for arbitrary anisotropic conductivities in the Fourier domain - Zhu, Yuzhen; Shao, Guihang; Wang, Xiudong; Zhang, Wenyan (Frontiers in Earth Science, 2023)
Previous studies have shown that anisotropy generally exists in geological bodies such as sedimentary rocks and fault zones, and more and more attention has been paid to the arbitrary conductivity media in surveys with the magnetotelluric sounding method. With the breakthrough development of computer hardware technology, large-scale 3D magnetotelluric modeling in anisotropic media has gradually become possible. At present, there are 3D magnetotelluric field simulation algorithms based on finite differences or finite elements for arbitrary anisotropic conductivity. In order to solve the common computational efficiency problems of the existing algorithms, we proposed a rapid 3D magnetotelluric forward approach for arbitrary anisotropic conductivity in the Fourier domain. Through the 2D Fourier transform, the governing equation can be converted from the space domain to the Fourier domain, thereby greatly reducing the calculation amount of the numerical simulation and improving the calculation efficiency. Then, the classical 1D anisotropy model is used to verify the correctness and the computational efficiency. Finally, the 3D anisotropic models of land and ocean are calculated, and the influence characteristics of the anisotropic medium on the magnetotelluric response are analyzed. The proposed algorithm will be used in the inverse imaging technique for large-scale 3D anisotropic data in future studies.